2022
DOI: 10.1016/j.eururo.2021.12.013
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2 Trial of the Effect of Antiandrogen Therapy on COVID-19 Outcome: No Evidence of Benefit, Supported by Epidemiology and In Vitro Data

Abstract: Background Men are more severely affected by COVID-19. Testosterone may influence SARS-CoV-2 infection and the immune response. Objective To clinically, epidemiologically, and experimentally evaluate the effect of antiandrogens on SARS-CoV-2 infection. Designs, settings, and participants A randomized phase 2 clinical trial (COVIDENZA) enrolled 42 hospitalized COVID-19 patients before safety evaluation. We also conducted a population-based ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 26 publications
0
50
0
Order By: Relevance
“… [25] Although it has been suggested that ADT decreases the risk of COVID-19 infection in patients with prostate cancer, [26] this was not supported by a recent meta-analysis and phase 2 trial. [ 27 , 28 ]…”
Section: Discussionmentioning
confidence: 99%
“… [25] Although it has been suggested that ADT decreases the risk of COVID-19 infection in patients with prostate cancer, [26] this was not supported by a recent meta-analysis and phase 2 trial. [ 27 , 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…Low total testosterone levels in men have been associated with hyper-inflammatory syndrome and respiratory failure 116 , and total testosterone levels are inversely associated with increased risk of ICU admission or death 92 ; thus, the (most probably transitory) hypogonadism caused by SARS-CoV-2 infection was suggested to promote severe outcomes 92 . In the COVIDENZA trial, including men and women >50 years old, the effect of the inhibition of testosterone signalling through enzalutamide on the outcome of hospitalized patients with COVID-19 was evaluated 117 . Overall, 42 patients were enrolled and randomized 2:1 to receive 5 days of treatment with enzalutamide or standard of care 117 .…”
Section: Testosterone and Androgen Deprivation Therapymentioning
confidence: 99%
“…In the COVIDENZA trial, including men and women >50 years old, the effect of the inhibition of testosterone signalling through enzalutamide on the outcome of hospitalized patients with COVID-19 was evaluated 117 . Overall, 42 patients were enrolled and randomized 2:1 to receive 5 days of treatment with enzalutamide or standard of care 117 . Patients treated with enzalutamide required longer hospitalization (hazard ratio for discharge from hospital: 0.43, 95% CI 0.20–0.93) than patients treated with the standard of care 117 .…”
Section: Testosterone and Androgen Deprivation Therapymentioning
confidence: 99%
See 2 more Smart Citations